1975
DOI: 10.1002/iroh.19750600601
|View full text |Cite
|
Sign up to set email alerts
|

Community patterns on a submerged barrier reef at Barbados, West Indies

Abstract: 1 quantitative survey of a submerged barrier reef n as undertaken in Barbados, Irest Indies, over a two year period . Photo-line transects were employed to obtain coverage data on corals and other benthic organisms. Light, sedimentation, currents, oxygen, temperature and salinity were also monitored.Results indicate corals cover about 30 per cent of the bottom with living colonies; another 7 per cent is contributed by other zoobenthos. The most abundant coral species are Montrtstretr nnnulnrin, N. CucertLoSn a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1976
1976
1994
1994

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Water could pass over and around a submerged site with relatively little difference in water motion between sides, allowing the formation of substrate and biota on the backreef similar to that found on the forereefs. Similarly, Ott (1975) reported that diversity patterns were nearly identical on inner and outer slopes at a submerged reef in Barbados. These findings suggest the significance of water motion in the community structure of coral reefs.…”
Section: Discussionmentioning
confidence: 82%
“…Water could pass over and around a submerged site with relatively little difference in water motion between sides, allowing the formation of substrate and biota on the backreef similar to that found on the forereefs. Similarly, Ott (1975) reported that diversity patterns were nearly identical on inner and outer slopes at a submerged reef in Barbados. These findings suggest the significance of water motion in the community structure of coral reefs.…”
Section: Discussionmentioning
confidence: 82%
“…For example, traps with high height to aperture ratios will be less subject to resuspension of their contents than shallower traps. Traps placed on or just above the substrate collect more sediments than those higher in the water column (Ott 1975). Mean sedimentation rates for reefs which are not subject to stresses from human activities range from less than 1 to about 10 mg cmp2 dC1 (Table 1).…”
Section: Historical Records Of Sedimentation On Coral Reefsmentioning
confidence: 99%
“…Coral reef systems are characterized by limited spatial and temporal variation in temperature, oxygen and salinity (Ott, 1975;Dana, 1976;Ohlhorst, 1980), but there are significant gradients in exposure to water movement, irradiance and disturbance (Roberts et al, 1977;Van den Hoek et al, 1978;Bak and Luckhurst, 1980). The possible response to such gradients in reproductive patterns of the dominant reef builders, the stony corals (Scleractinia), is essentially unknown.…”
Section: Introductionmentioning
confidence: 99%